Manajemen Keuangan Keluarga di Era Pandemi Covid 19 - Bunyamin Bunyamin (Jurnal Syntax Transformation, 2022)
The family as the smallest organizational unit has not been spared the impact of the COVID-19 pandemic. Not only health problems are affected but also financial problems. Therefore, it is important to manage and plan finances carefully and precisely so that the family's economic resilience is maintained. Management is basically the process of utilizing a number of organizational resources to achieve certain goals through the process of planning, organizing, directing and controlling. Finance in a family is one of the main foundations for building a calm and happy household. The purpose of this study is to discuss how to implement financial management in the family during the COVID-19 pandemic. This research method is a qualitative descriptive research. Then to analyze the data using the data that has been obtained in the form of previous research, then the data is analyzed in the sasi category and interpreted using the perspective of using documentary analysis. The result of this study is that family financial management is very important for the welfare of each individual and family in everyday life. Islamic financial management is the management of by determining priorities and household budgets.